Behavioral factors associated with delayed ART initiation among people living with HIV/AIDS (PLWH) in Nekemte referral Hospital, Western Ethiopia - Lami Bayisa; Abilo Tadesse; Diriba Mulisa; Ebisa Turi; Tadesse Tolosa (Elsevier, 2021)
Background: Delayed initiation of antiretroviral therapy (ART) continues to drive morbidity, mortality and onward human immune virus (HIV) infection transmission. The major causes for HIV related life threatening events were due to delayed ART initiation. Little has been documented about the timing of ART initiation in hospital settings where majority of patients present with advanced HIV disease and opportunistic infections, with a potentially high risk of mortality after discharge. So early initiation of ART is needed to reduce HIV related morbidity and mortality and to reduce HIV infection transmission, so the study aimed to determine PLWH's health belief factors related to delayed ART initiation. Methods: A hospital-based cross-sectional study was conducted to explore health-related beliefs among PLWH on delayed ART initiation at ART Clinic, Nekemte Referral hospital, Western Ethiopia between January 1, 2020 and March 31, 2020 for the time period from January 1, 2016 to December 31, 2019. Consecutive sampling method was used to recruit 417 PLWH. Patients were interviewed to obtain socio-demographic data. Relevant medical history was obtained from patients' chart records. The collected data were processed and analyzed using Epi data version 3.1 and SPSS version 20. Logistic regression models were constructed to identify independently associated behavioral factors with delayed ART initiation. P-value of <0.05 was used to declare the statistical significance. Result: The mean age of the 417 PLWH was 33.5 (SD±9.8) years. Most (>75%) of them were urban dwellers and attended formal education. A third (34%) of PLWH initiated ART delayed. Poor literacy status was significantly associated with delayed use of ART. Timing of ART initiation had significantly affected by respondents' perceived threat, perceived net benefit and self-efficacy to start ART there. Conclusion: Prevalence of delayed ART initiation was relatively low. Strengthening the mechanisms of early HIV test, linkage to care and awareness on ART benefit are recommended to initiate ART early.